Evaluating health promotion practice and methods - Thorogood, Margaret; Coombes, Yolande (Oxford : Oxford University Press, 2004)
This practical guide for practitioners of health promotion and public health describes methods by which health promotion can be evaluated. With examples given, it should help practitioners design and implement appropriate and informative evaluations.
Previous ed.: 2000.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health promotion -- Evaluation; Evaluation research (Social action programs)